1950
DOI: 10.4267/2042/69485
|View full text |Cite
|
Sign up to set email alerts
|

Stase veineuse et croissance osseuse

Abstract: Stase veineuse et croissance osseuse par M. SERVELLE, H. Sr. woNNET et H. LEBARs L'histophysiologie du tissu osseux est bien connue depuis long temps, de même que les facteurs infl" uenç. ant la croissance osseuse. Les actions hormonales ont été bien étudiées du point de vue physiologique. La glande thyroïde joue une action certaine sur la croissance des os. Les éthyroïdés sont des nains, les insuffi sances de croissance dans le myxoedème en sont une preuve. L'action de ]'hypophyse est indéniable. Les diverses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1967
1967
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In various studies no stimulation has been demonstrated (Wu andMiltner 1937, Keck andKelly 1965), while others have reported a slight stimulation (Pearse and Morton 1930, Bergmann 1931, Kishikawa 1936, Servelle 1948, Hutchinson and Burdeaux 1954, Colt and Iger 1963. In various studies no stimulation has been demonstrated (Wu andMiltner 1937, Keck andKelly 1965), while others have reported a slight stimulation (Pearse and Morton 1930, Bergmann 1931, Kishikawa 1936, Servelle 1948, Hutchinson and Burdeaux 1954, Colt and Iger 1963.…”
Section: Experimentcrl Investigationsmentioning
confidence: 99%
“…In various studies no stimulation has been demonstrated (Wu andMiltner 1937, Keck andKelly 1965), while others have reported a slight stimulation (Pearse and Morton 1930, Bergmann 1931, Kishikawa 1936, Servelle 1948, Hutchinson and Burdeaux 1954, Colt and Iger 1963. In various studies no stimulation has been demonstrated (Wu andMiltner 1937, Keck andKelly 1965), while others have reported a slight stimulation (Pearse and Morton 1930, Bergmann 1931, Kishikawa 1936, Servelle 1948, Hutchinson and Burdeaux 1954, Colt and Iger 1963.…”
Section: Experimentcrl Investigationsmentioning
confidence: 99%
“…There are probably several reasons why many investigators (Bore1 1922, Bergmann 1931, Kishikawa 1936, Servelle 1948, Hutchison & Burdeaux 1954, Colt & Iger 1963 have found venous stasis to be growth stimulating. In general, the series of animals used in most investigations were small.…”
Section: I82 Lars Ingvah Hansson Et Almentioning
confidence: 99%
“…Therefore the effect of venous ligation on longitudinal bone growth was studied. The femoral vein was chosen because it is readily accessible, and because ligation of this vein has been described as having a growth-stimulating effect (Borel 1922, Kishikawa 1936, Servelle 1948. The longitudinal bone growth was measured with the tetracycline tech-nique, making it possible to determine the growth per day with good accuracy (Hansson 1967).…”
mentioning
confidence: 99%
“…With regard to experimental equivalents, vascular deformities have been reproduced by many investigators such as Janes & Musgrove (1950), Hiertonn (1957), Doerr & Janes (1959), Kelly, Janes & Peterson (1959), Vanderhoeft, Kelly et al (1963). Venous stasis produced by vessel ligature or by tourniquet has been tried by, inter al, Borel (1922), Bergmann (1931, Kishikawa (1936), Servelle (1948), Hansson (1969, in press).…”
Section: B Survey Of the Literature Concerning Stimulation Of Skeletmentioning
confidence: 99%